Severe anaemia associated with Plasmodium falciparum infection in children: consequences for additional blood sampling for research. (December 2016) - Kuijpers, Laura; Maltha, Jessica; Guiraud, Issa; Kaboré, Bérenger; Lompo, Palpouguini; Devlieger, Hugo; Geet, Chris; Tinto, Halidou; Jacobs, Jan
Abstract Background Plasmodium falciparum infection may cause severe anaemia, particularly in children. When planning a diagnostic study on children suspected of severe malaria in sub-Saharan Africa, it was questioned how much blood could be safely sampled; intended blood volumes (blood cultures and EDTA blood) were 6 mL (children aged <6 years) and 10 mL (6–12 years). A previous review [Bull World Health Organ. 89: 46–53. 2011] recommended not to exceed 3.8 % of total blood volume (TBV). In a simulation exercise using data of children previously enrolled in a study about severe malaria and bacteraemia in Burkina Faso, the impact of this 3.8 % safety guideline was evaluated. Methods For a total of 666 children aged >2 months to <12 years, data of age, weight and haemoglobin value (Hb) were available. For each child, the estimated TBV (TBVe) (mL) was calculated by multiplying the body weight (kg) by the factor 80 (ml/kg). Next, TBVe was corrected for the degree of anaemia to obtain the functional TBV (TBVf). The correction factor consisted of the rate 'Hb of the child divided by the reference Hb'; both the lowest ('best case') and highest ('worst case') reference Hb values were used. Next, the exact volume that a 3.8 % proportion of this TBVf would present was calculated and this volume was compared to the blood volumes that were intended to be sampled. Results When applied to the Burkina Faso cohort, the simulation exercise pointed out that in 5.3 % (best case) and 11.4 % (worst case) of children the blood volume intended to be sampled would exceed the volume as defined by the 3.8 % safety guideline. Highest proportions would be in the age groups 2–6 months (19.0 %; worst scenario) and 6 months–2 years (15.7 %; worst case scenario). A positive rapid diagnostic test forP. falciparum was associated with an increased risk of violating the safety guideline in the worst case scenario (p = 0.016). Conclusions Blood sampling in children for research inP. falciparum endemic settings may easily violate the proposed safety guideline when applied to TBVf. Ethical committees and researchers should be wary of this and take appropriate precautions.